Antibody‐ and aptamer‐strategies for GvHD prevention. Issue 1 (29th October 2014) - Oelkrug, Christopher; Sack, Ulrich; Boldt, Andreas; Nascimento, Isis C.; Ulrich, Henning; Fricke, Stephan
Abstract Prevention of Graft‐versus‐Host‐Disease (GvHD) by preserved Graft‐versus‐Leukaemia (GvL) effect is one of the major obstacles following allogeneic haematopoietic stem cell transplantation. Currently used drugs are associated with side effects and were not able to separate GvHD from the GvL‐effect because of general T‐cell suppression. This review focuses on murine models for GvHD and currently available treatment options involving antibodies and applications for the therapeutic use of aptamers as well as strategies for targeting immune responses by allogenic antigens.